Influence of Indole Butyric Acid (IBA) on rooting and sprouting of semi hard wood cutting of olive (Olea europaea L.) - Nandre, B.M.; Kumar, Surendra; Shakhela, R.R.; Sharma, R.K. (Indian Journal of Agroforestry, 2020)
The present investigation was conducted at Agroforestry Research Station, S.D. Agricultural University Sardarkrushinagar (Gujarat) in the net house during the year 2012-2015 to determine the influence of eight concentrations of Indole Butyric Acid i.e. Control (uncontrolled i.e. without dip), 0 (water dip), 500, 1000, 1500, 2000, 2500 and 3000 ppm, with coco-pit and 5g N:P:K fertilizer (19:19:19) on rooting of olive stem cuttings. Pencil size semi hard wood cuttings of olive plant comprised of 4-6 nodes, 10-12 cm in length, all except 2-3 terminal leaves from cuttings were stripped off. The cuttings were dipped in above IBA solutions for 1 minute as â€œquick dipâ€ method before planting in rooting media. Among IBA concentrations, 3000 ppm concentration reset maximum shoot length (4.9, 17.4, 37.0 and 70.4 cm), shoot number (1.5, 1.8, 2.8 and 3.5), root length (7.8, 14.7, 30.4 and 62.6 cm), root number (2.9, 10.5, 11.6 and 12.3) at 3rd, 6th, 9th and 12th month of planting respectively; and wet root biomass (8.2 g), dry root biomass (3.0 g) and survival percentage (30.3 %) at 12th month of planting.